Study and Choice of Water Saturation Test Method for Tight Sandstone Gas Reservoirs - Liu, Cheng; Ma, Litao; Liu, Xueqing; Li, Yangbing; Zhang, Bo; Ren, Dazhong; Liu, Dengke; Tang, Xin (Frontiers in Physics, 2022)
This study aims at investigating the applicability of the commonly used water saturation test methods such as distillation extraction method, nuclear magnetic resonance (NMR) method, constant weight method, and Coulomb method in the water saturation test of tight sandstone gas reservoirs. The above methods were studied and optimized to overcome the difficulties of low water content determination caused by low porosity, low permeability, small pore throat, high capillary force, and high bound water saturation of tight sandstone, to obtain relatively accurate water saturation data. The results showed that the water content data determined by the constant weight method were consistent with the known water content saturation, and the average error was 3.6%. By shortening the echo interval, the average error of water content saturation tested by the NMR method for tight sandstone samples was 4.8%. The two methods of the distillation method and Coulomb method had large errors, and both failed to meet the requirements of water saturation determination of tight sandstone, of which the average error of the former was 27.9% and the average error of the latter was 50.7%. Therefore, for tight sandstone, the constant weight method and NMR method were recommended to be used for water content saturation testing, and the distillation extraction method and Coulomb method were not recommended. The research results provided a new method for the accurate determination of water content saturation in tight sandstone gas reservoirs.